Comunicação e saúde: reflexões sobre o Sistema Único de Saúde (SUS) em Palmas e a saúde digital durante a pandemia de Covid-19 - Viana, Cristiano Alves (2023)
This thesis aims to reflect on the application of digital health in the Unified Health System (SUS) during the COVID-19 pandemic, more specifically in the municipality of Palmas, Tocantins. For this purpose, the Collective Subject Discourse method was used, which seeks to understand the ways of thinking of a social group on a given topic. In this case, the relevant group are residents of the public housing condominium Residencial Parque da Praia, located in Palmas-Tocantins. The research set out to demonstrate and analyze the effects of digital health on the daily life of this community during the COVID-19 pandemic within the scope of the SUS. It also sought to understand the extent to which these people are included or excluded from the digital world, in addition to understanding their perception of digital health, SUS, the right to health and communication. The result of the research was obtained from the reproduction of the Collective Subject Discourse, that is, the collective opinion of the community on the topic of digital health. In general, the group considers itself relatively informed about health, SUS and social rights; most of this community makes use of Information and Communications Technology (ICT) and the internet in their daily lives. However, when it comes to using these resources to obtain information and request online health services, it was observed that digital health is still a distant reality for these SUS users.